Dietary Habit is Associated With Dysmenorrhea Among Adolescent - Sundari, Neti; Sari, Dian Nur Adkhana; Timiyatun, Endar; Kusumasari, Viantika (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Dysmenorrhea is pain during menstruation which is felt in the lower abdomen and back. The high incidence of dysmenorrhea in adolescents still does not get enough concern, even though it can cause a person to become weak, pale, reduce concentration, disturb daily activities, having a negative impact on quality of life. One of the factors that can cause dysmenorrhea is poor dietary habit. This study aims to analyze the correlation between dietary habit and dysmenorrhea in female adolescents. This type of research is quantitative, the number of samples are 262 respondents and the sampling technique was accidental sampling. Testing data using the Chi Square analysis test. From the results of the Chi Square analysis test, it was found that the value of p = 0.005 with a correlation value of 0.011, the study showed that there is a correlation between dietary habit with dysmenorrhea in female adolescent.